1991
DOI: 10.1159/000158885
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Measurement of Fixation Rate and Dimension Changes in the Aldehyde/Pressure-Fixed Canine Carotid Artery

Abstract: Excised canine carotid arteries held at constant physiologic length were cycled from –13 to +27 kPa with a constant-flow infusion pump, and the pressure-volume curves were recorded. The change in diameter on reducing the pressure from 16 to 0 kPa was determined and the strain of recoil [(diameter16 – diameter₀)/diameter16] calculated. Diameter recoil was reduced from 51 % (fresh tissue) to 5 % after 3 h pressure fixation in 4 % formaldehyde and to 9% after 15 min in 2% glutaraldehyde with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

1992
1992
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…Indeed, studies done in vivo and enhanced extracellular matrix involving principally colLrotid preparations involving interruption of flow and lagen (Cox, 1979;Milnor, 1982;Dobrin, 1983; Nichols & -ing static (and not pulsatile) pressure-diameter re-O' Rourke, 1990;Levy et al, 1994). Our present histomorhips have extensively shown that acute and long-term phometric findings in placebo-treated WKY and SHR were i-blockade relaxes arterial smooth muscle and increases obtained from the classical perfusion-fixation technique and compliance at any given value of transmural pressure were very similar to those previously reported in the literature umi et al, 1989;London et al, 1992;Levy et al, 1993;(Owens, 1985;Kratky et al, 1991;Benetos et al, 1993; Levy et The last possibility to consider is that the factors inal., 1994). Following chronic calcium blockade, decreased ig the present pulsatile pressure-diameter relationship medial thickness was observed in association with a substantial tly different from those modulating the static pressurereduction in elastin and collagen content, which however did whereas dilation transfers stresses to the elastic lamellae.…”
Section: Discussionsupporting
confidence: 89%
“…Indeed, studies done in vivo and enhanced extracellular matrix involving principally colLrotid preparations involving interruption of flow and lagen (Cox, 1979;Milnor, 1982;Dobrin, 1983; Nichols & -ing static (and not pulsatile) pressure-diameter re-O' Rourke, 1990;Levy et al, 1994). Our present histomorhips have extensively shown that acute and long-term phometric findings in placebo-treated WKY and SHR were i-blockade relaxes arterial smooth muscle and increases obtained from the classical perfusion-fixation technique and compliance at any given value of transmural pressure were very similar to those previously reported in the literature umi et al, 1989;London et al, 1992;Levy et al, 1993;(Owens, 1985;Kratky et al, 1991;Benetos et al, 1993; Levy et The last possibility to consider is that the factors inal., 1994). Following chronic calcium blockade, decreased ig the present pulsatile pressure-diameter relationship medial thickness was observed in association with a substantial tly different from those modulating the static pressurereduction in elastin and collagen content, which however did whereas dilation transfers stresses to the elastic lamellae.…”
Section: Discussionsupporting
confidence: 89%
“…After 1 or 2 minutes, a clamp was positioned on the atrium, and the fixation liquid was infused for 3 hours at a pressure equal to the MBP of each animal. 30 At the end of the perfusion, the thoracic aorta was dissected and preserved in a 4% formaldehyde solution until the histological study was performed.…”
Section: Morphological Studymentioning
confidence: 99%
“…30 For reasons explained in "Methods," the CSA rather than the thickness of the aortic media was chosen for evaluation of arterial hypertrophy. In the present study, the placebo-treated animals developed, as expected, significant medial aortic hypertrophy, with CSA values comparable to those observed in SHR of the same age.…”
mentioning
confidence: 99%
“…However, local pressures may become very high, causing vascular distension (Hodde & Nowell, 1980). Perfusion fixation before vascular casting can reduce such distension (Kratky et al, 1991), but at the risk of shrinking the vasculature or resulting in less complete casts (Reddy et al, 1995). We therefore chose to infuse the resin under pressure-controlled conditions, maintaining the input pressure at physiological levels.…”
Section: Discussionmentioning
confidence: 99%